Contemporary Craft Art On Jewelry: Case Study Of HS Silver Kotagede Company - Subiharto, Joko (Institut Seni Indonesia Yogyakarta, 2022)
Jewellery in the KBBI (Big Dictionary Indonesian) means items used for decoration, such as rings, earrings, bracelets and others. Jewellery is often created with gold and silver materials, so the price is relatively high according to the high cost of the material. Along with the times, jewellery evolved in design, material, function and technique. HS Silver is one of the silver jewellery companies in Kotagede Yogyakarta, which was founded in 1953 and still exists today. HS Silver Kotagede can survive and thrive today because it applies contemporary craft art styles to its designs and jewellery products. Contemporary craft art leads to various new concepts and visual forms that are developing in the present or present. Based on this, this study aims to: 1) determine the influence of contemporary craft art on HS Silver Kotagede jewellery products and 2). Describe modern jewellery products HS Silver Kotagede. Research methods use a descriptive qualitative approach. Data collection is carried out through literature study, field observation, interviews and documentation. The data obtained are analyzed interactively, consisting of data reduction, presentation and verification. The results showed that since the 1980s, the HS Silver company has adopted contemporary concepts and designs, also known as contemporary craft art. Various contemporary styles influenced the jewellery concept at HS Silver Kotagede in design and material aspects. The design takes specific themes from nature and the socio-culture of the surrounding community, such as the shape of a pineapple, bird cages and rockets. In addition to the design, there are changes in the materials used that do not only use the same but are also combined with other media such as ropes, resins, etc. Jewellery that uses contemporary craft art styles can open new trends and markets for HS Silver because the designs are fresher and more up-to-date. The results showed that since the 1980s, the HS Silver company has adopted contemporary concepts and designs, also known as contemporary craft art. Various contemporary styles influenced the jewellery concept at HS Silver Kotagede in design and material aspects. The design takes specific themes from nature and the surrounding community's socio-culture, such as the shape of a pineapple, bird cages and rockets. In addition to the design, there are changes to the materials used that do not only use the material but are also combined with other media such as ropes, resins and so on. Jewellery that uses contemporary craft art styles can open new trends and markets for HS Silver because the designs are fresher and more up-to-date.